Modeling the hydrolysis process of the bioethanol production - Gomes, Ranon de Souza; Carpes, Charles Quevedo; Lorenzzetti, Greice da Silva; Bortoli, Álvaro Luis de (VETOR - Revista de Ciências Exatas e Engenharias, 2013)
In this work, we model the hydrolysis process of the bioethanol production from vegetable sources. The process of bioethanol production described in this work allows the simultaneous use of various vegetables sources having starch or sugars, such as the rice, the potato, the cassava, the maize, the sugarcane, the beet, etc. The model developed considers the use of an enzyme for the conversion of the starch into saccharides. Numerical results are in agreement with experimental results found in the literature.